A multi-component wide distillation fuel (covering gasoline, jet fuel and diesel fuel) mechanism for combustion and PAH prediction. (15th November 2017) - Ren, Shuojin; Kokjohn, Sage L.; Wang, Zhi; Liu, Haoye; Wang, Buyu; Wang, Jianxin
Highlights: A reduced 11-component chemical mechanism is proposed for wide distillation fuel. The mechanism includes six classes of hydrocarbons and PAH pathways up to pyrene. The mechanism is validated for pure components, mixtures, surrogate and real fuels. A detailed soot model is coupled with the mechanism to predict the soot formation. The CFD simulations capture the engine combustion process and the soot formation. Abstract: A reduced 11-component ( n- heptane, iso -octane, toluene, ethanol, methanol, n -decane, n -dodecane, n- hexadecane, diisobutylene, cyclohexane and methyl-cyclohexane) chemical mechanism consisting of 178 species and 758 reactions is proposed for combustion and soot formation predictions of wide distillation fuel (WDF) covering gasoline, jet and diesel fuels. Six different classes of hydrocarbons (straight alkanes, branched alkanes, cycloalkanes, alkenes, aromatics and alcohols) are included in the present mechanism, which is constructed with a hierarchical structure. Optimizations based on sensitivity analyses are conducted for each sub-mechanism and the base mechanism. This reduced multi-component mechanism has been extensively validated against experimental data including ignition delay times, laminar flame speeds, species concentration profiles and new direct injection compression ignition (DICI) engine combustion data. The present mechanism is not only validated for each pure component, but also for different surrogate fuels for gasoline, jet fuel and diesel fuel. Measured ignition delay and laminar flame speed data for real fuels are also used to validate the present mechanism. The good agreement suggests the present mechanism can be used for simulation of multi-component surrogates of conventional transportation fuels. Furthermore, the present mechanism is used for multidimensional modeling studies to investigate the DICI combustion fueled with gasoline, diesel fuel and WDF. The experimental combustion characteristics as well as the soot and NOx emissions are all reasonably predicted, indicating the proposed mechanism can be applied for modeling in practical engine applications.